2004
DOI: 10.1210/me.2003-0436
|View full text |Cite
|
Sign up to set email alerts
|

Recruitment of β-Catenin by Wild-Type or Mutant Androgen Receptors Correlates with Ligand-Stimulated Growth of Prostate Cancer Cells

Abstract: Prostate cancers respond to treatments that suppress androgen receptor (AR) function, with bicalutamide, flutamide, and cyproterone acetate (CPA) being AR antagonists in clinical use. As CPA has substantial agonist activity, it was examined to identify AR coactivator/corepressor interactions that may mediate androgen-stimulated prostate cancer growth. The CPA-liganded AR was coactivated by steroid receptor coactivator-1 (SRC-1) but did not mediate N-C terminal interactions or recruit beta-catenin, indicating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
68
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(70 citation statements)
references
References 79 publications
1
68
1
Order By: Relevance
“…As a mediator of the steroid hormones testosterone and dihydrotestosterone, AR is an essential regulator of prostate growth and function. It has also been demonstrated that β-catenin, as well as TCF7L2 protein, can induce the expression of androgen regulated genes by binding to the AR (26,27). Considering the numerous interactions between Wnt and androgen signaling pathways, together with the growth regulatory role of TCF7L2 protein, we hypothesize that variation in the TCF7L2 gene can influence the development and progression of prostate cancer.…”
Section: Introductionmentioning
confidence: 86%
“…As a mediator of the steroid hormones testosterone and dihydrotestosterone, AR is an essential regulator of prostate growth and function. It has also been demonstrated that β-catenin, as well as TCF7L2 protein, can induce the expression of androgen regulated genes by binding to the AR (26,27). Considering the numerous interactions between Wnt and androgen signaling pathways, together with the growth regulatory role of TCF7L2 protein, we hypothesize that variation in the TCF7L2 gene can influence the development and progression of prostate cancer.…”
Section: Introductionmentioning
confidence: 86%
“…b-Catenin can enhance cell proliferation (Mulholland et al, 2003;Masiello et al, 2004), production of PSA and increase AR responsiveness to nonandrogen ligands, including estrogens (Truica et al, 2000;Pawlowski et al, 2002;Song et al, 2003b;Mulholland et al, 2003;. Mice with prostate-specific deletion of the b-catenin regulatory domain (Dexon 3) are reported to develop metaplasia and, in some instances, neoplastic transformation (Bierie et al, 2003;Gounari et al, 2002).…”
Section: Pi3k/akt and Ar: Critical Regulators Of Progression To Ai Prcamentioning
confidence: 99%
“…If PTEN mutational silencing and progressive reduction of GSK3b activity are key factors in promoting transcriptional promiscuity of AR, b-catenin/Tcf, AR/ b-catenin or AR/ARE (androgen response element) interactions could all serve as viable therapeutic options in progressive PrCa. However, as b-catenin appears to mediate increases in cell viability by coactivation of AR, rather than Tcf (Chesire et al, 2002;Masiello et al, 2004;, then small molecule targeting of regions necessary for AR/b-catenin interactions (i.e. b-catenin Arm repeats 5-6; AR LBD helices 3, 12) (Yang et al, 2002;Song et al, 2003a) could be promising.…”
Section: Summary and Future Directionsmentioning
confidence: 99%
“…Because of the critical role of these coregulators in the AR-mediated gene regulation, any dysregulation of AR:coregulator interactions may perturb normal physiology leading to disease conditions (22). This has been supported by the facts that critical AR interacting coregulators (steroid receptor coactivator-1 [SRC-1] and b-catenin) have been reported as prognosis or diagnostic markers in disease development and progressions (23). In addition, several types of mutations in the AR gene have been linked to endocrine dysfunctions (24).…”
Section: Androgen Receptor and Polymorphism Involving The Expansion Omentioning
confidence: 99%